PENGEMBANGAN BUKU PENGAYAAN NILAI-NILAI KONSERVASI HUMANISME DALAM PEMBELAJARAN MENULIS KREATIF CERITA FANTASI - Nonika Farahdila; Subyantoro Subyantoro (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2018)
Abstract: A good quality learning sources can support in the learning activity process to develop students' potential. Moreover, a good quality learning sources can attract and stimulate students' interest in learning. In accomplishing those objectives, books hold a strategic role. In that case, it is reasonable to make a development on an enrichment book which not only enriching knowledge, but also skills and shaping a positive personality in students. The purpose of this study is 1) to describe the needs of learners and educators of enrichment books; 2) drafting the enrichment book; and 3) outlining the expert's judgment of the enrichment draft. The content of conservation values of humanism is given in order to instill moral values. This research designs Research and Development (R & D) Thiagarajan model modified in 3 stages, such as define, design, and development. The results of this study are based on the results of questionnaire analysis needs of learners and educators who compiled into principles of book development. These principles include aspects of the material, aspects of presentation, aspects of graphics, aspects of language, aspects of learning materials needs creative writing fantasy story text, and aspects of the needs of the values of conservation of humanism. Abstrak: Sumber belajar yang berkualitas mendukung proses pembelajaran guna mengembangkan potensi peserta didik. Selain itu juga dapat menarik minat dan merangsang peserta didik untuk belajar. Untuk mencapai tujuan tersebut, buku memiliki peran strategis di dalamnya. Oleh karena itu, perlunya pengembangan buku pengayaan yang tidak hanya memperkaya pengetahuan tetapi juga mengembangkan keterampilan dan membentuk kepribadian positif peserta didik. Tujuan penelitian ini adalah mendeskripsi kebutuhan peserta didik dan pendidik terhadap buku pengayaan dan menyusun draf buku pengayaan serta menguraikan penilaian ahli terhadap draf buku pengayaan. Muatan nilai-nilai konservasi humanisme diberikan dengan tujuan untuk menanamkan nilai-nilai moral. Dengan desain Research and Development (R&D) model Thiagarajan yang dimodifikasi dalam 3 tahap, yaitu define, design, dan development dihasilkan prinsip-prinsip pengembangan buku. Prinsip-prinsip tersebut meliputi aspek materi, aspek penyajian, aspek grafika, aspek bahasa, aspek kebutuhan materi pembelajaran menulis kreatif teks cerita fantasi, dan aspek kebutuhan nilai-nilai konservasi humanisme.